A comparative study evaluating three line immunoassays available for serodiagnosis of equine Lyme borreliosis: Detection of Borrelia burgdorferi sensu lato-specific antibodies in serum samples of vaccinated and non-vaccinated horses. - Cornelia V Broeckl; Stephanie Hiereth; Reinhard K Straubinger (PLoS ONE)
Diagnosis of equine Lyme borreliosis (LB), an infection caused by members of the Borrelia burgdorferi sensu lato complex (Bbsl), is challenging due to the nonspecific clinical signs of the disease and due to the variety of non-standardized serological tests. Specific vaccine-induced antibodies against LB, providing an effective protection against the infection, complicate the issue further. The standard for the detection of specific antibodies against Bbsl is a two-tier test system based on an enzyme-linked immunosorbent assay (ELISA) or indirect fluorescent antibody test (IFA) for antibody screening combined with a qualitative, highly specific immunoassay (e. g. line immunoassay (LIA)) for confirmation. In this study, three LIAs available for detection of antibodies in equine serum samples were evaluated and compared. A total of 393 serum samples of 131 horses with known serostatus were used. It included groups of non-vaccinated horses, immunized horses (vaccinations against LB on days 0 and 14), and horses that had received an initial immunization plus an additional booster on day 180. Sera were collected on days 0, 135 and 210 of the study. Results were compared considering the tests' sensitivity, specificity, diagnostic outcome, and the operability of each test. Agreements of the diagnostic results among the LIAs were calculated for overall test results and single antigen-antibody-complex signal results. They are presented as inter-rater agreement and statistic reliability, represented by the Fleiss' kappa coefficient. Agreement scores ranged from poor to moderate depending on group and time-point of blood sample collection. Depending on LIA used, deficiencies were observed in the form of non-sufficient sensitivity of antigen signals on the LIA strips (especially for outer surface protein A (OspA) or variable major protein like sequence expressed (VlsE)) or as an inappropriate test interpretation of the OspA signal. Operability of the three LIAs was equally user-friendly with minor variations. In two LIAs, test-evaluation was simplified by a supplied scanner and evaluation software. To improve functionality of available LIAs for equine serum samples it is advisable to adjust sensitivity and specificity of single test antigen signals and establish appropriate evaluation protocols.